HPLC analysis and antimicrobial activity of Vitex altissima leaves extracts - Ajinza A; Arun A Rauf; Boby T Edwin (Plant Science Today, 2024)
The exploration of ethnomedicinal plants for phytochemical and pharmacological properties is crucial for developing novel therapeutics for chronic diseases. Vitex altissima, known as the Peacock chaste tree, is a significant member of the Verbenaceae family, is widely utilized in traditional medicine. This study investigates the phytochemical composition and antibacterial properties of V. altissima, a plant recognized for its medicinal use by various indigenous communities, including the Malayali tribes of Servarayan hills. The study involved extracting phytochemicals from the leaves of V. altissima using hexane, ethyl acetate and methanol through soxhlet extraction. The extracts were analyzed for secondary metabolites, including carbohydrates, proteins, amino acids, steroids, glycosides, alkaloids, tannins, phenolics, flavonoids, terpenoids, saponins, anthraquinones, oils and resins, diterpenes, phlobatannins and coumarins. Quantitative assessments of phenolic compounds, flavonoids and alkaloids were performed. Column chromatography was employed to fractionate the methanolic extract, resulting in 12 distinct fractions. These fractions were screened for antibacterial activity against E. coli, Klebsiella pneumoniae, Pseudomonas aeruginosa, Streptococcus mutans and Staphylococcus aureus using the agar well diffusion method. The minimal inhibitory concentration (MIC) was determined through a 2-fold serial dilution technique. High-performance liquid chromatography (HPLC) was utilized to identify the polyphenolic compounds responsible for antibacterial activity. Phytochemical screening revealed a diverse array of bioactive compounds in the extracts, with methanol extracts showing the highest total phenolic content (218 ± 7.21 mg GAE/g of extract) and significant antibacterial activity. The ethyl acetate extract exhibited the highest total flavonoid content (40.67 ± 6.65 mg QE/g of extract). Among the fractions, the column fraction from the chloroform-methanol gradient (VACF) demonstrated superior antimicrobial activity, particularly against S. mutans and P. aureginosa. The MIC values for VACF were 427 µg/mL for P. aeruginosa and 400 µg/mL for S. aureus, indicating potent antibacterial properties. HPLC analysis identified key polyphenolic compounds, including p-coumaric acid, ferulic acid and elagic acid, as the primary contributors to the antibacterial activity. The presence of these compounds aligns with the observed antimicrobial efficacy and highlights the potential of V. altissima extracts as a source of natural antibacterial agents.